Problems of learning english for IT students - Мороз Людмила; Moroz Liudmyla; Ясногурська Людмила; Yasnohurska Liudmyla; Данілова Наталія; Danilova Nataliia (Видавництво «Код», 2025)
Abstract. The article examines the problems of learning English faced by students of IT specialties, which are becoming increasingly relevant due to the growing role of English-language communication in the professional activities of information technology specialists. Learning English as a foreign language has its own specific features and may take place in group or individual formats, in groups with different levels of students’ language readiness. The refore, teachers need to find well-planned and well-organized ways to facilitate the teaching and learning process. Researchers have conducted a significant number of studies to address these issues and help teachers overcome their difficulties. This article provides a brief overview of teaching English as a foreign language and the reasons why IT students should be motivated to learn English, particularly through the development of critical thinking skills using discussion-based teaching methods. The article discusses the importance of professionally oriented instruction and offers strategies and methods that teachers can apply as tools to improve English-language learning among IT students. This can contribute to developing learners’ ability to use a foreign language to achieve specific functional goals depending on the characteristics of social and professional interaction: the situation, the status of interlocutors and the addressee, the language, and other factors related to the pragmatics of business communication. Attention is paid to developing students’ ability to correctly identify their audience by studying its needs, as well as understanding the purpose of IT communication, which involves analyzing the content, context, and expected outcomes of communication. The article also emphasizes the importance of fostering students’ self-directed learning skills, which are an essential component of a successful educational process, since they help learners not only to better absorb material but also to develop the ability to make independent decisions.

Резюме. У статті розглядаються проблеми навчання англійської мови студентів ІТ спеціальностей, які набувають особливої актуальності у зв’язку із зростаючою роллю англомовного спілкування у професійний діяльності спеціалістів в галузі інформаційних технологій. Вивчення англійської мови як другої або іноземної мови має свої особливості, відбувається у груповому або індивідуальному форматах, у групах з різним рівнем мовленнєвої готовності студентів, тому викладачам потрібно знайти добре сплановані та організовані способи, щоб полегшити процес навчання та викладання.
Проблеми навчання англійської мови студентів ІТ спеціальностей
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-17?authuser=0
Keywords: professionally oriented instruction; professional competencies; professional communication; methods and strategies of teaching English